Study on the Development of Urban Micro-Renewal Driven by Ethnic Culture-Taking Ebian Yi Autonomous County as an Example - Chen, Yinzhu (International Journal of Social Sciences and Public Administration, 2025)
Urban micro-renewal needs to rely on urban culture, and the Opinions on Strengthening the Protection and inheritance of History and Culture in Urban and Rural Construction, issued by the General Office of the Central Committee of the Communist Party of China (CPC) and the Genera Office of the State Council in 2021, pointed out the great significance of culture in urban and rural construction. Taking Ebian Yi Autonomous County as an example, this paper discusses the important role of ethnic culture in urban micro-renewal in ethnic areas and puts forward some development suggestions. At the same time, it also supplements the theoretical foundation for there search of urban micro-renewal model in ethnic minority areas.